Comparative study of the effect of heat on water balance in Desert sheep and Nubian goats - Abdel Latif, A.M. (1978)
Comaprative investigations have been made in a climatic room on the effects of periodic heat load (20-40°C), 3 days dehydration, rehydration, and feed type (Lucerne hay or grass hay) in adult Desert sheep and Nubian goats. The response to natural summer environment was also examined in groups of either species receiving grass hay and water ad libitum. Body temperature regulation, body weight changes, water relations, dry matter. Intake and digestion and blood and urine composition were the parameters studied. On exposure to 40°C the increases in rectal tempeature, skin temperature and respiratory rate were more pronounced in goats than in sheep. In the outdoor environment the species response was reversed and coincided with the diurnal fluctuations in ambient temperature and solar radiation. The feed type had no significant effect on temperature regulation although the goats maintained significantly higher panting rates with grass hay. Dehydration resulted in higher rectal and skin temperatures and lower respiratory rates irrespective of species and feed type; this response was reversed during rehydration. On heat exposure there was a sharp rise in body weight during the first 3 days and thereafter decreased progressively with grass hay whereas it was almost maintained with Lucerne hay. During dehydration with both feeds the goats experienced higher body weight losses than sheep. On rehydration the lost body weight was compensated only in animals receiving Lucerne hay. Drinking was the major avenue of water intake and the beat induced increase was more pronounced in goats than in sheep. The increase in water intake was correlated with hyperthermia and the level of protein intake. Higher urine excretion was induced by heat stress and higher protein intake indicating thermolytic diuresis and excretion of excessive nitrogenous waste products respectively. On dehydration urine excretion decreased progressively in both species but to a higher extent in goats particularly with grass hay. Rehydration did not induce marked diuresis in both species with Lucerne hay; with grass hay there was complete water retention in sheep while the goats did not retain the whole volume ingested during rehydration. The faecal water loss was positively related to dry matter intake. During periodic heat load exposure it decreased in both species with grass hay and increased in sheep only with Lucerne hay. During dehydration the reduction in faecal water loss resulted from a decrease in the amount of moisture per unit of faeces as well as an actual decrease in faeces output due to decrease in dry matter intake. On periodic heat load exposure, with grass hay, evaporative water loss was increased to the same extent in both epecies whereas with Lucerne hay the increase was more marked in goats. Apparently the feed type had no significant effect on evaporative water loss. In both species the water turnover rates were significantly increased on heat exposure and were higher with Lucerne hay than with grass hay. The response to heat was more pronounced in goats. With grass hay as staple food the turnover rate values were higher at 20-40°C than in the outdoor environment in both species. Periodic heat load depressed the dry matter intake in goats only with Lucerne hay whereas with grass hay there was a decline in both species. Irrespective of the environment the goats had higher dry matter intake with Lucerne hay whereas in sheep there was no significant feed effect. In both species dehydration depressed the food intake to a higher extent with Lucerne hay than with grass hay. Both species had higher dry matter digestibility values with Lucerne hay. In both species the water/dry matter ratio increased with heat exposure and was higher with Lucerne hay than with grass hay. An exception was that goats had a higher ratio with grass hay at 20-40°C because of loss of condition and low heat tolerance. In animals maintained outdoors there was a significant positive correlation between were intake and dry matter intake. The change which occurred in blood volume and composition were modulated mainly by haemodilution resulting from heat exposure or rehydration and haemoconcentration following dehydration, and the goats showed higher responses under most of the experimental situations. However, some of the parameters were separately affected by feed type and heat. The values of haematocrit, total plasma solids, total plasma proteins, plasma albumin, and plasma urea were higher with Lucerne hay with grass hay in both species. Irrespective of species and feed type acute heat exposure resulted in an increase in circulating plasma solids and plasma urea concentration. The changes in urine electrolytes were generally affected by body fluids dynamics. On dehydration urine sodium potassium and urea concentrations increased irrespective of species and feed type. However, whereas the daily output of sodium was elevated the outputs of potassium and urea went down. Under all experimental conditions urine urea concentration and total daily excretion were higher in animals fed on Lucerne hay. The results obtained which were related to mechanisms involved in temperature regulation and water relations were discussed in the light of previous findings in the literature.